PENGARUH BANTUAN PROGRAM KELUARGA HARAPAN (PKH) TERHADAP MOTIVASI BELAJAR SISWA SMP N DI KECAMATAN PANGEAN - Sundri, Ila Bermi; Nas, Sakdanur; Syabrus, Hardisem (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract:This study aims to determine the effect of the family of expectations programs on increasing the learning motivation of SMPN students in Pangean district. The population in this study mere all junior high school in Pangean who received PKH, as foe the number of samples in this study as many as 84 students receiving PKH. The sampling technique as total sampling for students who received PKH assistance so that the sample obtained was 84 students from 69 family cards. Data analysis technique used by author in quantitative analysis and product moment correlation. The results of the study showed that there was a significant and positive effect between the family hope program assistance on the learning motivation of SMP N students in Pangean district ad evidenced by the probability value <0,05(0,000<0,05) then Ha was accecpted. The results of the study show that the family hope program assistance contributes 27,8% to learning motivation.Keywords: The Influence of The Hope Family Program Assistance (PKH), Students’ Learning Motivation.